HUBUNGAN SELF EFFICACY DENGAN TINGKAT KECEMASAN PADA PASIEN INFARK MIOKARD - Budi Rustandi; Rizki Gumilang (Sekolah Tinggi Ilmu Kesehatan Rajawali, 2020)
Background : Anxiety is common in patients with acute cardiovascular disease. Self-reported increase in anxiety levels is up to 20% -50% in patients with myocardial infarction. It takes a strong self-efficacy from within a person to recover from coronary heart disease, although basically this disease cannot be cured. Research Objectives : This study aims to determine the relationship of self-efficacy to anxiety in patients with myocardial infarction at Al Ihsan Hospital, West Java Province. Methods : This study design used quantitative non-experiment with a cross-sectional approach. Respondents in this study were 110 respondents using non probability sampling technique, namely purposive sampling. The research instrument used the Zung Self-Rating Anxiety Scale (SAS / SRAS) questionnaire and the Self Efficacy questionnaire. Bivariate analysis using the Chi Square test to determine the relationship between variables. Results : The results showed that most of the patients experienced mild anxiety in myocardial infarction patients as many as 82 respondents (74.5%), patients with low anxiety were 28 respondents (25.5%), while most of the respondents with high self-efficacy were 82 respondents. respondents (74.5%) and low self-efficacy as many as 28 respondents (25.5%). Chi Square test results obtained value (p = 0.001 <0.05). Conclusion : There is a significant relationship between self-efficacy and anxiety levels in patients with myocardial infarction at the Heart Polyclinic at Al Ihsan Hospital, West Java Province with a p-value of 0.001.